"Wer kennt nicht die Almé der Egyptier?" Benedikte Naubert's Alme oder Egyptische Mährchen (1793–97) and Women Storytellers. (8th June 2021) - Koser, Julie
Abstract : The figure of the almé, an Egyptian female storyteller and entertainer, held sway over the European imagination for centuries, when images of the nebulous "Orient" were conjured by artists, authors, and explorers. Eschewing the eroticized depictions of this figure popularized in European travelogues and narratives, Benedikte Naubert portrays her eponymous narrator as a learned woman. Naubert articulates the perils women faced when they asserted themselves as storytellers. Also, her emphasis on the female storytelling tradition offers a model for contemporary women writers, by laying claim to the respected figure of the almé . The collection's narrator, Almé Rusma, constructs a community of women storytellers that transcends cultural and temporal borders and asserts that women's stories are worth telling.